Chromosome 8 Polysomy Accounting for MYC Over-Expression in Angiosarcoma Arising as Somatic-Type Malignancy in Metastatic Teratoma. Case Report. (June 2022) - Vargas, A. Cristina; Grimison, Peter; Joy, Christopher; Garrone, Bernadette; Bonar, Fiona; Ghahan, Raha Madadi; Davidson, Trent; Maclean, Fiona M.
MYC over-expression by immunohistochemistry (IHC) is utilised in routine pathology practice as a surrogate marker for MYC amplification, which plays a key oncogenic role in post-irradiation and chronic lymphedema-associated angiosarcoma. We present the case of a 32-year old male, who presented with high-grade angiosarcoma arising in a background of metastatic testicular teratoma. IHC for MYC showed strong nuclear expression in the angiosarcoma cells prompting the consideration of post-irradiation-induced angiosarcoma but our patient did not undergo radiotherapy. Fluorescence in-situ hybridization (FISH) excluded MYC amplification and instead showed Chromosome 8 polysomy, which accounted for the strong MYC IHC expression present, not previously described in the context of germ cell tumours. The occurrence of MYC over-expression due to polysomy illustrates a novel clinical scenario (angiosarcoma arising as somatic malignancy) where strong MYC IHC expression can be found in the absence of underlying amplification or prior radiotherapy exposure.